2011
DOI: 10.1007/s00540-011-1095-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of rocuronium–sugammadex, an alternative to succinylcholine, as a muscle relaxant during electroconvulsive therapy

Abstract: We compared the recovery time from neuromuscular blockade induced by rocuronium combined with sugammadex versus succinylcholine during electroconvulsive therapy (ECT). Anesthesia was induced using propofol, followed by succinylcholine (1 mg/kg) or rocuronium (0.6 mg/kg). Immediately after the seizure stopped, 16 mg/kg sugammadex was infused. Neuromuscular monitoring was performed and continued until recovery of the train-of-four ratio to 0.9. We compared the recovery time of T1 to 10 and 90% between groups. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 12 publications
0
38
1
2
Order By: Relevance
“…Lee et al [2,3] reported that reversal of profound rocuronium (1.0-1.2 mg/kg)-induced neuromuscular block with a large dose of sugammadex (16 mg/kg) was significantly faster than spontaneous recovery from SCC. Previously, we showed the potential benefit of using rocuronium (0.6 mg/kg)-sugammadex (16 mg/kg) as an alternative to SCC (1 mg/kg) for muscle relaxation during ECT [4]. A large dose of rocuronium (1.0-1.2 mg/kg) is usually not needed for muscle relaxation during ECT, as shown in our previous study [4] and that of others [1].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Lee et al [2,3] reported that reversal of profound rocuronium (1.0-1.2 mg/kg)-induced neuromuscular block with a large dose of sugammadex (16 mg/kg) was significantly faster than spontaneous recovery from SCC. Previously, we showed the potential benefit of using rocuronium (0.6 mg/kg)-sugammadex (16 mg/kg) as an alternative to SCC (1 mg/kg) for muscle relaxation during ECT [4]. A large dose of rocuronium (1.0-1.2 mg/kg) is usually not needed for muscle relaxation during ECT, as shown in our previous study [4] and that of others [1].…”
Section: Introductionmentioning
confidence: 80%
“…Previously, we showed the potential benefit of using rocuronium (0.6 mg/kg)-sugammadex (16 mg/kg) as an alternative to SCC (1 mg/kg) for muscle relaxation during ECT [4]. A large dose of rocuronium (1.0-1.2 mg/kg) is usually not needed for muscle relaxation during ECT, as shown in our previous study [4] and that of others [1]. Hence, we speculated that a slightly smaller dose of sugammadex would be required for equally rapid recovery from 0.6 mg/kg rocuronium-induced muscle relaxation as from relaxation with 1 mg/kg SCC.…”
Section: Introductionmentioning
confidence: 99%
“…Sugammadeksin son zamanlarda kullanıma girdiği bir diğer uygulama da elektrokonvulsif tedavi olmuştur. Çok kısa süreli bir işlem olması nedeniyle, nöromuskuler blok için süksinilkolinin tercih edildiği bu uygulamada, gerek süksinilkolinin istenmeyen yan etkilerinden kaçınmak, gerekse psodokolinesteraz eksikliği olan hastalarda rokuronyum kullanılarak, sugammadeksin hemen uygulanabilir ve hızlı etkileri ön plana çıkmakta ve bu hastalarda giderek daha yaygın kullanıma yol açmaktadır [13][14]. Bizim çalışmamız ve daha önce değinilen, benzer çalışmalarla da desteklenen sonuçlara göre, sugammadeksin muskarinik yan etkilerden uzak bir şekilde güvenli ve nöromusküler blok düzeyi ne kadar derin olsa da uygun dozda kullanımı ile hızlı bir şekil-de etkin olduğu bir gerçektir.…”
Section: Discussionunclassified
“…After convulsion of mECT, 0 % of TOFR is considered. Then we administered 4 mg/kg of sugammadex and the value of TOFR reached 100 % [3]. After 2 min of administration…”
Section: Abstract Rocuronium · Sugammadex · Tof · Mectmentioning
confidence: 99%